The Next Practice of Sustainability Innovation for Business Leaders in the VUCA Era: A Community Enhancement Program - Jacquelinda Sandra Sembel; Linggadjaya, Restiana Ie Tjoe (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
Sustainability innovation has become critical for businesses to achieve sustainable competitive advantage in a world full of volatility, uncertainty, complexity, and ambiguity (VUCA). Thus, businesses need to develop strategic plans by looking beyond the best practices to the next practice of sustainability innovation and inspire human resources through coaching. The community enhancement program aims to inspire the participants to explore creative ways to integrate sustainable innovation strategies, such as cutting-edge green technologies, innovative green business models, and strong leadership, that can build resilience, drive long term growth, and empower the role of leaders as coaches. By engaging in active discussions, participants can gain valuable insights into implementing effective and scalable sustainable innovation practices and leading with a coaching approach, that will ultimately contribute to a more resilient and sustainable future.